Exploring The Application of Generative Artificial Intelligence (Gen-AI) at EFL Primary Class in Kuta District - I Putu Gede Suardika (Indonesian Postgraduate Foreign Language Education Association, 2024)
Generative Artificial Intelligence is a human made system which involves a computerize system, information and database. Generative AI can be in form of machine learning or other tools that able to create authentic text, audio, code, images, simulation and video content. The use of generative AI (genAI) in language learning is increasing during or post pandemic of Covid-19. Especially in EFL primary learners, generative AI becoming a new trend that help teachers and students more active in learning. This study is aimed to find out what type of generative AI used by the EFL primary teachers and what are their perspectives on the generative AI. Through the survey and interview on 40 English primary teachers in Kuta, it is found that 9 teachers were using generative AI such as text content creation, image creation and sound creation in their English class. The 31 teachers did not apply the generative AI in their class; they are more familiar with Microsoft office and Canva. Regarding to the teachers' perspective is showed 75% of the teachers have a good believe on generative AI is helpful and make the class more interactive.